1995
DOI: 10.1093/jac/36.suppl_a.43
|View full text |Cite
|
Sign up to set email alerts
|

A compilation of meropenem tissue distribution data

Abstract: Meropenem body fluid and tissue concentration data from both published studies and samples obtained during efficacy evaluation have been compiled and presented according to a consistent format to facilitate comparison. The concentration data have been compared with the mode MIC data available for the pathogens isolated during the clinical evaluation of meropenem. These data support the widespread and rapid penetration of meropenem into the interstitial fluid of those tissues not protected by a tight epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Like other b-lactam antibiotics, imipenem has some penetration into the CSF, and greater permeability with meningeal inflammation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Like other b-lactam antibiotics, imipenem has some penetration into the CSF, and greater permeability with meningeal inflammation [2].…”
Section: Introductionmentioning
confidence: 99%
“…A dose of 40 mg/kg/8 h in children with bacterial meningitis produces concentrations in the CSF of between 0·9 and 6·5 mg/l, which far exceed the minimum inhibitory concentration (MIC 90 ) of the microorganisms that most commonly cause community‐acquired meningitis. This is the recommended dose, with a maximum of 2 g/8 h (Hutchinson et al , 1995). Meropenem penetrates the CSF well when the haematoencephalic barrier is inflamed.…”
Section: Evolution Of Analytical Alterations During and After Meropenmentioning
confidence: 99%
“…No specific protein-binding studies have been reported in the literature, but the manufacturer reports the protein binding of meropenem to be approximately 2%.8, 92 The agent appears to be widely distributed in various body tissues and fluids (Table 4). 12' 66* [95][96][97][98][99][100][101][102] Penetration into the cerebrospinal fluid (CSF) results in drug concentrations ranging from below 1% of simultaneous plasma concentrations in patients with intact uninflamed meninges, to 52% of simultaneous plasma concentrations after administration of single intravenous doses of 20-40 mgkg to adults and children with inflamed meninges.95 Penetration into the CSF is, as may be expected, related to the size of the dose; patients with acute bacterial meningitis receiving 20-mg/kg doses achieved meropenem CSF concentrations of 0.1-2.8 mg/L, and 40-mgkg doses resulted in concentrations ranging from 0.33-6.5 m g L g 5 One case report of an adult receiving 6 g/day observed mean Cmin and C,,, of 0.5 mg/L and 1.6 mg/L, respectively. lo3 Although its penetration into the CSF varies considerably among individuals, guinea pig models of bacterial meningitis showed the drug to be effective in the treatment of infections due to penicillin-sensitive S. pneumoniae, E. coli, P aencginosa, L. monocytogenes, N. meningitidis, and H. influenzae.lo4 Consistent with both pharmacokinetic data and animal models, the agent also is effective i n the treatment of meningitis in clinical studies in humans.…”
Section: Pharmacokine Ticsmentioning
confidence: 99%